PENGARUH METODE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TERHADAP MOTIVASI BELAJAR BAHASA JAWA - Aisah, Anita; Alsa, Asmadi (Universitas Ahmad Dahlan, 2016)
AbtractMotivation to learn of Java Language in elementary school students is low. This will negatively impact the declining apreciation students to the Javanese culture that should be preserved. To overcome the lack of motivation to learn of Java Language takes an interesting learning method is a method of learning in groups. The method will use in this research is a method of student team achievement division (STAD). This study aimed to determine the effect of the implementation of STAD method to motivate students to learn of Java Language. This research will used untreated control group design pretest and posttest. The results of statistical tests using mixed design Anova showed a highly significant difference between the experimental group before and after the application of learning methods STAD (sig 0,002<0,01). In addition there is a significant difference between the experimental group and the control group with sig (0,002) < 0,01.Keywords : elementary school student, method of student team achivement divisionmotivation to learn